Capacitación en técnica vocal para un grupo de jóvenes cantantes de la ciudad de piñas y presentación en el marco del proyecto mes de las artes y la cultura – agosto 2021 del gobierno autónomo descentralizado municipal de Piñas. - Cuenca Ortiz, Daniela Fernanda (2022)
Music is considered one of the best forms of expression, it manifests the culture of a people that encompasses the subjectivity of the author and the interpreter. In addition, in all artistic activities, technical vocal work enhances talent and achieves an improvement in the study and training of singers, as it focuses on the importance of knowing how to take care of and develop the voice; it also allows us to understand the conformation of the phonatory organs and how sounds are emitted so beautifully. The present work was to give a workshop on vocal technique to young talents in Piñas community. The general objective of this project was to contribute to development of the vocal abilities of popular singers and to strengthen their insertion in the cultural projects of the Autonomous Decentralised Municipal Government of Piñas. Interviews, documents studies and descriptions of the facts that were presented in the investigated reality were carried out in order to discover the processes and results of the object of study, with the intention of finding out what difficulties the singers had with respect to the techniques necessary for the development of the voice. Didactic guides were also provided, which included vocal strategies and techniques, with the intention of contributing to the improvement of the research, contributing to the society of Piñas canton. It is recommended that the governmental institutions of the city of Piñas to follow up and pay attention to the artistic and cultural needs of the young talents of the aforementioned city, and also include in the annual agenda developed by the Municipal Government of Piñas, the organisation of short-term projects to train young talents in vocal techniques, holding seminars, forums and, above all, workshops that provide opportunities for training and artistic development.